On the Relationship between Intrinsic Saliency and Implicit Learning of Apologetic Strategies: The Case of Taiwanese EFL Learners - Chin-Ting Liu; Yuan-shan Chen (MDPI AG, 2021)
The current study explored the relationship between the intrinsic saliency of apologetic strategies and the effects of implicit learning. Seventeen Taiwanese English as a Foreign Language (EFL) learners with intermediate proficiency participated in the experiment with a pretest on apology in the first week, a noticing session in the second week and a posttest in the third week. The results from the noticing session indicated that providing reasons (e.g., taking on responsibility/explanation or account) and offer of repair were more salient in input to those learners. Additionally, the use of the apologetic strategies taking on responsibility and offer of repair increased in the posttest. Taken together, the results indicated that higher degrees of saliency in input led to better implicit learning outcomes. The interplay between input saliency and explicit/implicit learning as well as the pedagogical implications were discussed.